Fractal and Multi-Fractal Analyses of the Geomagnetic Field Variations Caused by the Earthquake on January 24, 2020 in Turkey - Onishchenko, A.; Chernogor, L.; Lazorenko, O. (My University, 2022)
With usage of the Wavelet Transform Module Maxima method and the Multi-Fractal Detrended Fluctuation Analysis method, the set of traditional and original multi-fractal numerical characteristics was estimated. Combining the fractal and multi-fractal analyses results with ones for the time-frequency structure, obtained the Continuous Wavelet Transform application, the set of disturbances caused by the earthquake was discovered. For these disturbances, all needed time-frequency, fractal and multifractal characteristics were estimated. The disturbances were shown to be fractal ultra-wideband processes with complex, non-stationary multi-fractal structure. Two promising candidates for the role of earthquake precursors were revealed. One possible earthquake precursor in both horizontal components of the geomagnetic field time variations seems to be detected. This precursor was shown to be registered 25.5 hours before the earthquake event. Being be found in time variations of the multi-fractal characteristics only for both horizontal components of the geomagnetic field, another possible earthquake precursor took place 0.5 hours before the earthquake event. The so-called transition of the multi-fractal process to the monofractal mode was detected. For both precursors, the time-frequency, fractal and multifractal characteristics were estimated.
Keywords: Fractal Ultra-Wideband Process; Geomagnetic Field Time Variations; Earthquake; Multi-Fractal Analysis; Fractal Analysis; Fractal Ultra-Wideband Process